A group decision making model with hybrid intuitionistic fuzzy information. (September 2015) - Yue, Zhongliang; Jia, Yuying
Highlights: A TOPSIS-based method is used in group decision making. The model deals with hybrid intuitionistic fuzzy information. The distance measure in TOPSIS technique is replaced by projection measure. There are no transformations between hybrid intuitionistic fuzzy information. Abstract: Group decision making (GDM) is among the most important activities that usually occurs in our daily life. This paper extends the TOPSIS (technique for order performance by similarity to an ideal solution) approach to deal with hybrid intuitionistic fuzzy information. Using a projection measure instead of a distance measure, the separations between each alternative decision and its ideal decisions are established in a hybrid intuitionistic fuzzy environment. There are no transformations between intuitionistic fuzzy numbers and interval-valued intuitionistic fuzzy numbers. The alternatives are ranked directly based on original information. An experimental analysis is used to illustrate the feasibility and practicability of introduced method.